The Implementation of Kurikulum Merdeka as The Newest Curriculum Applied at Sekolah Penggerak in Indonesia - Andi Asrifan; Prodhan Mahbub Ibna Seraj; Andi Sadapotto; Nurhumairah; K. J. Vargheese (CV. Eureka Murakabi Abadi, 2023)
This research was conducted to describe the implementation of Kurikulum Merdeka at Sekolah Penggerak and to analyze the obstacles faced in the of Kurikulum Merdeka at Sekolah Penggerak. Sekolah Penggerak in this research were SDN 2 Timoreng Panua and SDN 2 Sereang and the respondents were the principal and 2 learning committees in each school. So in total there are 6 respondents. The data collection procedure uses observation and interview that is semi-interview. This research uses qualitative methods as a research methodolgy. The implementation of Kurikulum Merdeka at SDN 2 Timoreng Panua and SDN 2 Sereang has entered its second year of implementation. Schools have begun to adapt to this new curriculum. The preparation of the KOSP has been carried out since the beginning of the Kurikulum Merdeka implementation. Then, it follows the making of teaching modules and the implementation of assessments. Because it is a new thing, of course there are obstacles faced by the school in its implementation. Especially at the beginning of the implementation of the Kurikulum Merdeka due to the lack of knowledge regarding the implementation of this Kurikulum Merdeka. However, the school continues to try to minimize the obstacles faced